A Novel Perovskite SrTiO3‐Ba2FeNbO6 Solid Solution for Visible Light Photocatalytic Hydrogen Production. Issue 2 (22nd September 2016) - Zhang, Guoqiang; Sun, Shaorui; Jiang, Wenshuai; Miao, Xiang; Zhao, Zhao; Zhang, Xiaoyan; Qu, Dan; Zhang, Duoying; Li, Dabing; Sun, Zaicheng
Abstract : Mixing elements on the B site in ABO3 results perovskite with narrow band gap. Ba2 FeNbO6 exhibits band gap of 2.29 eV by using two elements. SrTiO3 ‐Ba2 FeNbO6 solid solution displays a good visible light photocatalytic activity by promoting the charge separation process.